2-(6-Methyl-2,3,4,9-tetrahydro-1H-carbazol-1-ylidene)propanedinitrile - Sekar, M. (International Union of Crystallography, 2011)
In the title compound, C(16)H(13)N(3), the cyclohexene ring adopts a sofa conformation. An intramolecular N—H⋯N hydrogen bond generates an S(7) ring motif. In the crystal, the molecules are linked by pairs of N—H⋯N interactions, forming centrosymmetric dimers with an R (2) (2)(14) motif.